2010
DOI: 10.1111/j.1524-4725.2009.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Surgical Treatment of Nonmelanoma Skin Cancer of the Head and Neck in Greece

Abstract: Surgical resection achieves a satisfactory NMSC clearance rate in the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
40
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 38 publications
7
40
2
3
Order By: Relevance
“…Men generally have up to 2 times higher rate of BCC [9, 10, 16]. In our study, when the whole head and neck region is encountered, there was no statistically significant difference between men (55%) and women (45%) that was consistent with other studies [10, 13, 17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Men generally have up to 2 times higher rate of BCC [9, 10, 16]. In our study, when the whole head and neck region is encountered, there was no statistically significant difference between men (55%) and women (45%) that was consistent with other studies [10, 13, 17].…”
Section: Discussionsupporting
confidence: 92%
“…According to our findings, more than half of the lesions are found in the nose (32.3%), orbital (19.1%), and cheek (18.1%) areas which are the most central and prominent parts of the entire head and neck region. These regions are also more prone to chronic sunlight exposure [2, 5, 10, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…2,13 In fact, NMSC were the most common malignant skin neoplasms, affecting mainly elderly patients, as previously described . [14][15][16][17] In most studies, male sex is reported as predominant, however in our patients the opposite was observed. 6,8,16,18 BCC represented over two thirds of all NMSC and predominated over SCC on all skin areas, except for the lower lip and the genital area.…”
Section: Discussioncontrasting
confidence: 49%
“…[14][15][16][17] In most studies, male sex is reported as predominant, however in our patients the opposite was observed. 6,8,16,18 BCC represented over two thirds of all NMSC and predominated over SCC on all skin areas, except for the lower lip and the genital area. In the former, SCC predominance is probably explained by its particular anatomic disposition, nearly perpendicular to the solar radiation, potentiating the effect of UV light.…”
Section: Discussioncontrasting
confidence: 49%
“…Our cases peaked at seventh decade. Although age at admission was consistent with the literature in our country, peak age was seventh decade, similar to that in countries such as Greece, Spain and Italy (10)(11)(12). Despite most of the people living in this region have light colored skin and eye, advanced peak age can be attributed to healthy diet like in European countries (13).…”
Section: Discussionsupporting
confidence: 89%